Funkcija avtorskega pripovedovalca v noveli Rotschildova violina A. P. Čehova - Skaza, Aleksander (Slavistična revija, 2006)
The study examines the function of the authorial narrator in the novella Rothschild's Violin in the formation of both the literary character (particularly from the point of view of the "inner man") ant the two-part novella plot with dramatic novella turnabout and unexpected finale.
Keywords: 2. pol. 19. str.; 2nd half of 19th century; authorial narrator; avtorski pripovedovalec; comicality; eng; inner man; komika; little man; mali človek; notranji človek; novela; novelistični preobrat; novella; novella turn; Pukin, Anton Pavlovič; Rotschildova violina; Rotschild's violin; ruska književnost; Russian literature; tragedy; tragika